Issues connected with the constitution of the adoption of adults: analysis from Spanish Private International Law - Sánchez Cano, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Based on the study of Law 54/2007, on international adoption and after having examined the substantive legislation on adoption in Spain, this paper deals with the analysis of some of the controversial issues that arise regarding adoptions of adults and emancipated minors, from the Private International Law perspective and specifically with regard to the constitution of adoption by the Spanish authorities.